2010
DOI: 10.1111/j.1600-6143.2009.02858.x
|View full text |Cite
|
Sign up to set email alerts
|

IFN‐γ Triggered STAT1‐PKB/AKT Signalling Pathway Influences the Function of Alloantigen Reactive Regulatory T Cells

Abstract: (current address) * Corresponding authors: Kathryn J. Wood, kathryn.wood@nds.ox.ac.uk; Bin Wei, weibin@sibs.ac.cn

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 29 publications
0
39
1
Order By: Relevance
“…In contrast, effective inhibition of alloresponses seems to depend on alloantigen-specific Treg cells (6,34). It is now emerging that IFN-g production by natural Treg cells can be important for their suppressive function in transplantation by autocrine activation through IFN-g receptor signaling (35). Such autocrine activation may also explain why it is so important that IFN-g is produced by the Treg cells themselves to inhibit acute GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, effective inhibition of alloresponses seems to depend on alloantigen-specific Treg cells (6,34). It is now emerging that IFN-g production by natural Treg cells can be important for their suppressive function in transplantation by autocrine activation through IFN-g receptor signaling (35). Such autocrine activation may also explain why it is so important that IFN-g is produced by the Treg cells themselves to inhibit acute GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ acts on activated Treg to induce STAT1, which in turn induces t-bet and IFN-γ expression [120,121].…”
Section: Role Of Ifn-γ In Induction Of Antigen Specific Tregmentioning
confidence: 99%
“…In mice, a subpopulation of Tregs was described that produced IFN-␥ after phorbol 12-myristate 13-acetate (PMA)/ionomycin stimulation [5]. Murine IFN-␥-producing Tregs inhibited skin graft rejection, whereas Tregs generated in IFN-␥-deficient mice as well as Tregs deficient of the IFN-␥ receptor exhibited impaired suppressive function and ability to control skin graft rejection [6,7]. It was demonstrated that the inhibition of skin graft rejection was mediated by the IFN-␥-triggered STAT1-PKB/AKT signaling pathway [7].…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the inhibition of skin graft rejection was mediated by the IFN-␥-triggered STAT1-PKB/AKT signaling pathway [7]. Furthermore, CD4 ϩ Foxp3 ϩ T cells of mice tolerized by pretreatment with donor alloantigen under the cover of anti-CD4 antibody produced significantly higher levels of IFN-␥ than CD4 ϩ Foxp3 ϩ T cells of naive animals [7]. Several authors reported on both IL-17 and IFN-␥ expression of induced or natural murine Treg [8 -11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation